Civic engagement and the arts and humanities: A UK perspective. (July 2015) - Gallagher, Tony
Higher education in the UK is in a state of flux and this is having particular impact on the humanities. On the one hand, the pressure to support a STEM agenda is seen by some as forcing higher education down a narrow economic agenda, while government requirements for assessing the social and economic impact of research have raised concerns about excessive utilitarianism and a downgrading of 'disinterested enquiry'. This paper argues that these concerns may be misplaced. The research impact agenda has the potential to promote more socially engaged research and more democratic engagement in the creation and dissemination of knowledge. In the US, concerns about the democratic role of higher education more often seem to focus on the student experience. By contrast, in the UK concerns about citizenship education and democratic participation more often focus on high school students, perhaps because university students are more likely to have a formal role in institutional governance. This paper concludes that the papers in this forum have a very American feel, but the issues they address resonate on a much wider scale.